2022
DOI: 10.3390/foods11131899
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis and Near-Infrared Hyperspectral Reflectance Imaging for the Determination of Blueberry Bruise Grading

Abstract: Bruising of the subcutaneous tissues of blueberries is an important form of mechanical damage. Different levels of bruising have a significant effect on the post-harvest marketing of blueberries. To distinguish different grades of blueberry bruises and explore the effects of different factors, explicit dynamic simulation and near-infrared hyperspectral reflectance imaging were employed without harming the blueberries in this study. Based on the results of the compression experiment, an explicit dynamic simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The compression speed of the texture analyzer was set to 0.5 mm/s. According to previous studies, blueberries were heavily damaged when compressed to a distance >2.5 mm (Zheng et al, 2022), and the heavy damage was easily observed. In this experiment, blueberries subjected to a force of 5 N would be compressed to a distance >2.5 mm.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…The compression speed of the texture analyzer was set to 0.5 mm/s. According to previous studies, blueberries were heavily damaged when compressed to a distance >2.5 mm (Zheng et al, 2022), and the heavy damage was easily observed. In this experiment, blueberries subjected to a force of 5 N would be compressed to a distance >2.5 mm.…”
Section: Methodsmentioning
confidence: 87%
“…It was known from the study of Section 3.2 that the stack method of unit cell d was the best. As shown in Table 6, the maximum browning area of ULB in unit cell was 32.1%, the blueberry was slightly damaged (Zheng et al, 2022). According to commercial standards, sales were not affected when the damaged area of the blueberry did not reach 35%, the maximum force that caused the damaged area was 5.3 N. If the blueberries were stacked in the best way, the ULB in the bottommost unit cell was subjected to the greatest force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To distinguish different grades of blueberry bruises, Zheng et al (2022) used near-infrared hyperspectral reflectance imaging to get the actual bruising rate of blueberries. The actual damage rate of blueberries was 1.1% with the optimized parameters.…”
Section: Visible/near-infrared Spectroscopy Detection Technologymentioning
confidence: 99%
“…A total of 146 blueberries in good shape and with similar freshness and no visual defects (cuts, shrivel, etc.) were selected for the experiment, which lasted for 10 days (Zheng et al, 2022). To keep the blueberries fresh, the samples were stored in a refrigerator at 5 • C until the experiments were conducted.…”
Section: Samples Preparation and Data Collectionmentioning
confidence: 99%